MAIN PROBLEMS OF TEACHING THE RUSSIAN LANGUAGE AND WAYS TO SOLUTION THEM. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article presents the teacher's view on the main problems of teaching Russian language and literature today and his own experience in overcoming the identified problems.